The effects of various forms of rehabilitation on patients with lower limb ischemia - Szymczak, Maria; Majchrzycki, Marian; Stryła, Wanda; Lisiński, Przemysław (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Intermittent claudication is one of the most distinctive symptoms in Peripheral Arterial Disease (PAD),which causes gradually increasing muscle pain in the lower limbs during physical activity. Guided kinesiotherapy of patients suffering from intermittent claudication is an integral part of the treatment. Aim of the Study. The paper discusses various forms of exercises used in the treatment of intermittent claudication. Conclusions. The most common form of rehabilitation of patients with PAD is unassisted treadmill training in a home environment or assisted treadmill training. Alternative options include strength exercises of the lower limbs, osteopathic techniques, stationary bike exercises or the combination of the mentioned methods. The alternative methods of rehabilitation have a positive effect on PAD patients; however, their efficacy has been studied only recently. Due to the lack of reliable data in peer-reviewed journals it is difficult to establish which of the alternative methods is the most effective. The effects of treadmill training have been studied for many years and have been widely reported in science journals. Currently, treadmill training is considered to be the most effective, evidence-based, form of rehabilitation of patients with intermittent claudication
Keywords: intermittent claudication; lower limb ischemia; rehabilitation